Freedom from Choice? The Rollout of Person-centered Disability Funding and the National Disability Insurance Scheme - Hall, Tania; Brabazon, Tara (INKLUSI, 2020)
Person-centered funding models are replacing block-funding models in the disability services sector.  Australia is part of this international trend.  Concerns have been raised by service providers, suggesting that people with disabilities are not benefiting from this system.  This paper evaluates the views of service providers from a large non-government organization in South Australia, responsible for leading the transition from a block-funded model of support to a person-centered model of support.  Two focus groups were conducted.  Two themes emerged from these focus group discussions: customers with disabilities are vulnerable in the market, and marketizing disability services compromises quality.  Neoliberal ideologies and market-based values frame the challenges and opportunities for not-for-profit organizations when transitioning to person-centered funding for disability support.  This research both enlivens and confirms the existing research literature.  Although person-centered funding models offer a socially just model, there is evidence that unintended consequences emerge in an open and competitive quasi-market.  This study reveals that the competitive market design had stopped trans-sector collaboration. [Saat ini, model pendanaan berbasis orang banyak menggantikan model pendanaan-blok di sektor layanan disabilitas. Australia adalah bagian dari tren internasional ini. Lembaga layanan sosial khawatir bahwa para difabel tidak akan mendapatkan manfaat dari sistem ini. Artikel ini meninjau pandangan penyedia layanan dari organisasi non-pemerintah besar di Australia Selatan. Dua FGD dilakukan dalam riset ini. Dua tema muncul dari FGD: pelanggan difabel mengalami kerentanan di pasar dan ‘swastanisasi’ layanan disabilitas mengganggu kualitas. Ideologi neoliberal dan nilai berbasis-pasar menyajikan tantangan dan peluang bagi organisasi nirlaba ketika beralih ke pendanaan berbasis orang dalam layanan disabilitas. Penelitian ini mengonfirmasi literatur penelitian yang sudah ada. Meskipun model pendanaan berbasis orang menawarkan model yang adil secara sosial, ada bukti bahwa konsekuensi yang tidak diinginkan dapat muncul dalam pasar kuasi terbuka dan kompetitif. Studi ini mengungkapkan bahwa desain pasar yang kompetitif telah menghentikan kolaborasi lintas sector.]